2021
DOI: 10.7717/peerj.11765
|View full text |Cite
|
Sign up to set email alerts
|

Structural and immunological characterization of an epitope within the PAN motif of ectodomain I in Babesia bovis apical membrane antigen 1 for vaccine development

Abstract: Background Bovine babesiosis caused by Babesia bovis (B. bovis) has had a significant effect on the mobility and mortality rates of the cattle industry worldwide. Live-attenuated vaccines are currently being used in many endemic countries, but their wide use has been limited for a number of reasons. Although recombinant vaccines have been proposed as an alternative to live vaccines, such vaccines are not commercially available to date. Apical membrane antigen-1 (AMA-1) is one of the leading candidates in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Due to the fact that the vaccines currently being administered are neither fully safe nor effective, researchers have extensively searched for a candidate vaccine antigen that could be used to develop an effective vaccine against B. bovis (4). As has been found with BbAMA-1, studies of its immunogenicity demonstrated its vaccine potential (12,36,37). However, a lack of in-depth knowledge and understanding of the immunological characterization of the response may have implications for the design and assessment of AMA-1-based vaccines for bovine babesiosis.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Due to the fact that the vaccines currently being administered are neither fully safe nor effective, researchers have extensively searched for a candidate vaccine antigen that could be used to develop an effective vaccine against B. bovis (4). As has been found with BbAMA-1, studies of its immunogenicity demonstrated its vaccine potential (12,36,37). However, a lack of in-depth knowledge and understanding of the immunological characterization of the response may have implications for the design and assessment of AMA-1-based vaccines for bovine babesiosis.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the ectodomains I and II region of BbAMA-1 has been successfully expressed as a doublet band corresponding to around 48 kDa. Because BbAMA-1 encompasses the extracellular cysteine-rich domains I and II ( 12 , 36 , 37 ). It is likely that cysteine oxidation and formation of intra-molecular disulfide bonds is responsible for the doublet formation in Laemmli SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations